Design Considerations for CMOS-Integrated Hall-Effect Magnetic Bead Detectors for Biosensor Applications - Skucha, K. (2013)
We describe a design methodology for on-chip magnetic bead label detectors based on Hall-effect sensors. Signal errors caused by the label-binding process and other factors that limit the minimum detection area are quantified and adjusted to meet typical assay accuracy standards. The methodology is demonstrated by designing an 8192 element Hall sensor array, implemented in a commercial 0.18 μm CMOS process with single-mask postprocessing. The array can quantify a 1% surface coverage of 2.8 μm beads in 30 seconds with a coefficient of variation of 7.4%. This combination of accuracy and speed makes this technology a suitable detection platform for biological assays based on magnetic bead labels.